2020
DOI: 10.1093/scan/nsaa073
|View full text |Cite
|
Sign up to set email alerts
|

Common neural and transcriptional correlates of inhibitory control underlie emotion regulation and memory control

Abstract: Abstract Inhibitory control is crucial for regulating emotions and may also enable memory control. However, evidence for their shared neurobiological correlates is limited. Here, we report meta-analyses of neuroimaging studies on emotion regulation, or memory control and link neural commonalities to transcriptional commonalities using the Allen Human Brain Atlas (AHBA). Based on 95 functional magnetic resonance imaging studies, we reveal a role of the right infer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…Next, we contrasted the Think condition with the No-Think condition and found the increased activity for the Think condition in a set of regions including the medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), hippocampus, inferior parietal lobule (IPL), precuneus, angular gyrus, and cerebellum (voxelwise Z>3.1, cluster-level p < .05 FWER corrected) (Figure 1F; Table S2). Together with the behavioral results from the final memory test, these results confirmed that participants in our experiment followed task instructions, leading to univariate neural signatures of memory retrieval and suppression consistent with prior findings (Anderson, 2004;Levy and Anderson, 2012;Anderson and Hanslmayr, 2014), as well as recent meta-analyses of memory suppression (Guo et al, 2018;Liu et al, 2020b).…”
Section: Fmri Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Next, we contrasted the Think condition with the No-Think condition and found the increased activity for the Think condition in a set of regions including the medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), hippocampus, inferior parietal lobule (IPL), precuneus, angular gyrus, and cerebellum (voxelwise Z>3.1, cluster-level p < .05 FWER corrected) (Figure 1F; Table S2). Together with the behavioral results from the final memory test, these results confirmed that participants in our experiment followed task instructions, leading to univariate neural signatures of memory retrieval and suppression consistent with prior findings (Anderson, 2004;Levy and Anderson, 2012;Anderson and Hanslmayr, 2014), as well as recent meta-analyses of memory suppression (Guo et al, 2018;Liu et al, 2020b).…”
Section: Fmri Resultssupporting
confidence: 88%
“…Cognitive and neural models of memory retrieval and suppression suggest that successful retrieval could be the result of cooperation between an inhibitory control network and an episodic retrieval network (Rugg and Vilberg, 2013), while effective suppression depends on top-down control of the inhibitory control network upon an episodic retrieval network (i.e., competition) (Anderson and Hanslmayr, 2014). Previous fMRI studies of memory suppression supported this idea by showing that compared to Think trials, No-Think trials are associated with stronger activation in control-related regions including the dorsolateral prefrontal cortex, ventrolateral prefrontal cortex, inferior parietal lobule, and supplementary motor area (Anderson, 2004;Guo et al, 2018;Liu et al, 2020b). At the same time, these activity increases are accompanied by reduced activity in memory-related areas in the medial temporal lobe, including the hippocampus (Anderson and Hanslmayr, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite investigating very different phenomena, these studies reported similar sets of significant GO categories, most frequently implicating categories related to metabolic, neuronal, and generic biological and behavioral processes. The most reported GO category in our survey was 'chemical synaptic transmission' (GO:000726), which has been reported in 15 human analyses from 10 different studies (21,26,32,(69)(70)(71)(72)(73)(74)(75) and four different mouse analyses from three different studies ( organization of human resting-state functional connectivity (21), human adolescent cortical shrinkage and myelination (26), and tract-traced structural connectivity in the mouse brain (17). Some other commonly reported categories include 'potassium ion transmembrane transport' (22,26,32,74,77,78), 'learning or memory' (15,74,75,79,80), and 'electron transport chain' (18,19,23,26,74)…”
Section: Diverse Phenotypes In the Literature Are Enriched For Similamentioning
confidence: 69%
“…However, it should be noted that although the N2 component has widely been associated with inhibitory control of TBF items in the DF procedure (Anderson & Hanslmayr, 2014; Liu et al., 2020), there are also findings suggesting that the N2 reflects other cognitive processes rather than inhibition (e.g., conflict resolution or information discarding of TBF items; Schindler & Kissler, 2018). Furthermore, when considering the intrinsic tendency of mnemic neglect in healthy populations, we propose that it is possible the observed DF effect for negative social feedback mainly resulted from selective rehearsal of TBR items rather than the inhibitory control of TBF ones.…”
Section: Discussionmentioning
confidence: 99%